Penggunaan Sistem Informasi Geografis (SIG) untuk Manajemen Bencana Pasca-Bencana - Zulhuda, Rahmania; Ellia, Adinda Putri; Putri, Hesti Amelia; Ikhwan, Ikhwan (Indo-MathEdu Intellectuals Journal, 2025)
Natural disasters in Indonesia pose significant challenges in managing their impacts, especially during the crucial post-disaster phase for long-term recovery. Geographic Information Systems (GIS) offer significant potential in supporting post-disaster management through the integration and analysis of spatial data. This literature study aims to assess the use of GIS in post-disaster management, as well as to identify the challenges and development opportunities. Data collection was conducted through literature studies and document analysis, including scientific journals, disaster agency reports, and relevant government policies. The obtained data were analyzed using content analysis techniques. The results of the analysis indicate that GIS plays a crucial role in damage assessment, planning for aid distribution, inter-agency coordination, and recovery monitoring. Nevertheless, challenges such as data integration, limitations in infrastructure and human resources, and data security need to be addressed. The development opportunities for GIS are supported by technological advancements, increased data availability, and awareness of disaster issues. Optimal utilization of GIS requires continuous efforts in data standardization, capacity building, and policy strengthening to achieve more effective and responsive post-disaster management.